Importance of load frequency in applying cyclic loads to investigate ballast deformation under high-speed train loads. Issue 120 (May 2019) - Zhang, Xu; Zhao, Chunfa; Zhai, Wanming
Abstract: Railway ballast is now subjected to dynamic train loads with higher frequency components due to the continue increase of the train speed. However, the effect of load frequency on ballast permanent deformation was ignored in most laboratory tests. This study aims to clarify the importance of load frequency in applying cyclic loads to investigate the ballast permanent deformation under high-speed rail loading conditions. A three-dimensional discrete element model was established using clumps with realistic ballast particle shapes and validated with a laboratory test. Numerical simulations were then conducted with the validated DEM model to study the ballast deformation behavior. The simulated ballast deformation under high-speed train loads and that under cyclic loads with different load frequencies were compared to demonstrate the quantitative discrepancy between them. The results from this study confirm that under high-speed rail loading scenarios, the load frequency has significant influence on ballast permanent deformation and there is significant importance to take the effect of the load frequency into account when investigating the permanent deformation of high-speed railway ballast by applying cyclic loads. It is recommended to apply the cyclic loading with the same amplitude to the high-speed train load and with the frequency equivalent to the passing frequency of the train's wheelbase to the ballast in laboratory tests so as to obtain quantitative ballast deformation results by using one load cycle to simulate two axle loads of a train. Highlights: A three dimensional discrete element model with realistic ballast particle shapes is established. Permanent deformation of ballast under repeated high-train loads are simulated using discrete element method. Discrepancy between the ballast deformation results under train loads and those under cyclic loads are analyzed. Cyclic loading for achieve quantitative ballast deformation in laboratory test is recommended.